From Surau to Social Media: Nusantara Ulama’s Da'wah Transformation in The Society 5.0 Era - Afrijaludin, Muhammad; Annisa Nurfajrina; Sofia Zaeti Nur Siregar; Muhammad Chepy Rhevy; Abdul Fadil (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
The transformation of da‘wah in the Nusantara demonstrates a significant shift from the traditions of surau and pesantren to digital platforms with the emergence of Society 5.0, which integrates human interaction and technology within a new ecosystem of religious communication. This shift raises critical questions about how the moderate, contextual, and locally grounded da‘wah values of Nusantara ulama adapt to a digital landscape that is rapid, open, and often vulnerable to distortions of religious authority. This study analyzes the transformation of da‘wah from traditional spaces to digital spheres, identifies enduring values within Nusantara ulama’s da‘wah tradition, and examines the challenges and opportunities of digital preaching in the 5.0 era, employing a literature review with a descriptive analytical qualitative approach through the examination of academic publications from 2015 to 2025. The findings reveal that digital da‘wah offers broad accessibility and creative modes of delivering religious messages while presenting challenges such as fragmented authority, content commercialization, and the proliferation of non-scholarly preaching, indicating the need to internalize traditional values such as hikmah (wisdom), tawazunb(balance), and tasamuh (tolerance) to maintain ethical da‘wah practices in online spaces. In conclusion, the digital transformation of Nusantara ulama’s da‘wah represents not merely a shift in medium but a process of recontextualizing core values to cultivate digital da‘wah that is moderate, ethical, and relevant to the needs of 21st-century society.